Human-Nature Reciprocity in C.S. Lewis's The Lion, the Witch and the Wardrobe: An Ecocritical Analysis - Salma, Sifa; Haryanti, Rahayu Puji (JELITA, 2025)
This study explores the reciprocal relationship between humans and nature in C.S. Lewis’s The Lion, the Witch and the Wardrobe through an ecocritical lens, using Greg Garrard’s theoretical framework. Employing a qualitative method, the research focuses on two major themes from Garrard's ecocriticism: wilderness and dwelling. The analysis examines ecological values conveyed through character interactions, symbolism, and narrative structure. The findings reveal that nature in the novel functions as a setting and a moral agent capable of influencing human behavior and values. Human actions depicted through the Pevensie siblings and their interactions with the natural world directly impact the ecological balance within the story. This study contributes to ecocritical scholarship by foregrounding the active role of nature in a literary work often overlooked in environmental studies. It highlights children’s fantasy literature as a valuable medium for promoting ecological awareness and ethical reflection on human-nature interdependence.